`Sexy yes, obesity no': the role of vloggers in influencing diet food purchase with self-openness moderation - Purwanto P.; Rahayu S. (Cogent Business & Management, 2024)
This study aims to evaluate the patterns by which vloggers influence consumers' purchase intention for sustainable healthy diet food, to prevent obesity. In this process, a model was developed and validated through a collaboration between the lens of similarity-attraction theory (SAT) and the health belief model (HBM). This emphasized the effect of health behaviour similarity and perceived susceptibility-severity, which increased para-social interaction (PSI) and consumer purchase intention on TikTok social media viewers. Furthermore, the moderating effect of self-openness was examined on health behaviour similarity with PSI and consumers' purchase intention. The role of gender and marital status was also assessed in supporting the relationship between health behaviour similarity (HBS) and PSI. In this case, a total of 438 validated samples were tested using the Covariance-based SEM approach. Based on the results, HBS and perceived susceptibility severity (PSS) were positively related to PSI and consumers' purchase intention. PSI was also positively related to consumers' purchase intention. Additionally, self-openness played a role in moderating the relationship between health behaviour similarity to PSI and purchase intention. These results subsequently considered the effectiveness of digital celebrity support for young people in sustainable healthy diet behaviour, especially married and unmarried women.
Keywords: 650; health behaviour similarity; perceived susceptibility-severity; Psi; self-openness; consumers' purchase intention